Sustained knowledge work and thinking time amongst academics: gender and working from home during the COVID-19 pandemic. (2nd January 2022) - Peetz, David; Baird, Marian; Banerjee, Rupa; Bartkiw, Tim; Campbell, Shelagh; Charlesworth, Sara; Coles, Amanda; Cooper, Rae; Foster, Jason; Galea, Natalie; de la Harpe, Barbara; Leighton, Catherine; et al.
ABSTRACT: The COVID-19 pandemic triggered a migration of workforces to work from home. A key issue for academics was the implications for the ability to carve out 'thinking time' to engage in what we term sustained knowledge work, the type of work essential for producing research. We administered an employee survey to academics from seven Australian and seven Canadian Universities, receiving over 3000 responses. We report on both quantitative and qualitative findings from the survey, with a particular emphasis on the latter. The two countries displayed broadly similar patterns in responses, but these patterns were gendered in specific ways. We distinguished between episodic and sustained knowledge work and found the shift of the location for sustained knowledge work from the workplace to the home affected academics unevenly, with disproportionate negative impacts on women. There are implications for all knowledge workers: while gendered, domestic norms continue to exist, the sustained knowledge work that is critical to career advancement can become especially problematic for women knowledge workers.